The Global Tracheostomy Collaborative: one institution's experience with a new quality improvement initiative. (January 2016) - Lavin, Jennifer; Shah, Rahul; Greenlick, Hannah; Gaudreau, Philip; Bedwell, Joshua
Abstract: Objective: Given the low frequency of adverse events after tracheostomy, individual institutions struggle to collect outcome data to generate effective quality improvement protocols. The Global Tracheostomy Collaborative (GTC) is a multi-institutional, multi-disciplinary organization that utilizes a prospective database to collect data on patients undergoing tracheostomy. We describe our institution's preliminary experience with this collaborative. It was hypothesized that entry into the database would be non-burdensome and could be easily and accurately initiated by skilled specialists at the time of tracheostomy placement and completed at time of patient discharge. Methods: Demographic, diagnostic, and outcome data on children undergoing tracheostomy at our institution from January 2013 to June 2015 were entered into the GTC database, a database collected and managed by REDCap (Research Electronic Data Capture). All data entry was performed by pediatric otolaryngology fellows and all post-operative updates were completed by a skilled tracheostomy nurse. Tracked outcomes included accidental decannulation, failed decannulation, tracheostomy tube obstruction, bleeding/tracheoinnominate fistula, and tracheocutaneous fistula. Results: Data from 79 patients undergoing tracheostomy at our institution were recorded. Database entry was straightforward and entry of patient demographic information, medical comorbidities, surgical indications, and date of tracheostomy placement was completed in less than 5 min per patient. The most common indication for surgery was facilitation of ventilation in 65 patients (82.3%). Average time from admission to tracheostomy was 62.6 days (range 0–246). Stomal breakdown was seen in 1 patient. A total of 72 patients were tracked to hospital discharge with 53 patients surviving (88.3%). No mortalities were tracheostomy-related. Conclusion: The Global Tracheostomy Collaborative is a multi-institutional, multi-disciplinary collaborative that collects data on patients undergoing tracheostomy. Our experience proves proof of concept of entering demographics and outcome data into the GTC database in a manner that was both accurate and not burdensome to those participating in data entry. In our tertiary care, pediatric academic medical center, tracheostomy continues to be a safe procedure with no major tracheostomy-related morbidities occurring in this patient population involvement with the GTC has shown opportunities for improvement in communication and coordination with other tracheostomy-related disciplines.